A method to partition the relative effects of evaporative cooling and shading on air temperature within vegetation canopy. Issue 1 (10th July 2018) - Tan, Puay Yok; Wong, Nyuk Hien; Tan, Chun Liang; Jusuf, Steve Kardinal; Chang, Mei Fen; Chiam, Zhi Quan
Abstract: The cooling effects of vegetation in urban areas are generally attributed to two distinct processes: shading by vegetation canopy and evaporative cooling (EC) by evapotranspiration. An important knowledge gap in using vegetation to moderate urban temperatures is the relative importance of these two processes at different spatial scales. Information is particularly limited at the individual tree level. The current state of knowledge prevents more informed decisions on the selection of trees species for more effective urban cooling. This paper reports on a method developed to evaluate the relative importance of shading versus EC on air temperatures within the canopy of small potted trees. A replicated field study was conducted to assess the relative effects of these two processes on a commonly used urban tree species in the tropics. By comparing temperature differences at different positions in the canopy, and controlling transpiration through withholding water and by severing stems of the trees, the study demonstrated a method to partition the effects of shading compared with transpiration. Both shading and EC effects peaked around midday when solar radiation was the highest. The latter effect was shown to contribute ∼29% to the lower air temperature within the canopy compared with the temperature above the canopy. We suggest that the method reported in this study can be scaled up to larger specimens or replicated to other species to improve our knowledge of species differences in these two processes within canopies of urban trees.